The effect of spontaneous emission on the VCSEL laser output polarizatio - Burov, Leonid I.; Gorbatsevich, Alexander S.; Lobatsevich, Pavel M. (Journal of the Belarusian State University. Physics, 2017)
Based on the earlier developed approach, a study of the spontaneous emission effect (b factor) on polarization switching has been performed to describe the formation of polarized radiation in surface-emitting semiconductor lasers (VCSEL). As shown by the results of simulation, a good agreement with the experimental data is observed in the range β ∼ 10–5–10– 6. In this case one can neglect possible β deviations when the injection current variations occur.